Experimental investigation on the influence of phase change material on the output performance of thermoelectric generator. (November 2021) - Wang, Jun; Song, Xiangxiang; Ni, Qiqiang; Li, Xingjun; Meng, Qingtian
Abstract: Thermoelectric generators (TEGs) can convert heat into electricity directly. However, the thermal boundary conditions are intermittent and high temperature in most TEG systems. Therefore, thermal management of TEG systems is of great significance. It is an efficient technology to use phase change material (PCM) for thermal management of the TEG systems. PCM is applied to hot side of TEG in this study, and the phase change material-thermoelectric generation (PCM-TEG) system is set up. For the purpose of exploring the effect of the PCM on the output performance of TEG, the common TEG system is established to compare with PCM-TEG system. Furthermore, the effect of the heat transfer characteristics of PCM on TEG output performance is investigated and discussed in detail under different pulse transient thermal boundary conditions. Experimental results show that PCM can reduce the temperature fluctuation to protect TEG and extend the temperature difference operation time. The PCM of solid state, solid-liquid coexistence state and liquid state have different effects on reducing the temperature fluctuation. Besides, the PCM-TEG system cannot provide the peak output power provided by the common TEG system, but it is still beneficial to provide a stable output power. Highlights: An experimental system is set up for studying the application of PCM for thermal management of TEG systems. Heat transfer characteristics of PCM under different pulse transient thermal boundary condition are discussed. The effect of PCM applied to TEG hot side on the output performance is investigated. PCM is very useful for reducing voltage fluctuations and providing a stable power output.